A novel curcumin analog binds to and activates TFEB in vitro and in vivo independent of MTOR inhibition. Issue 8 (2nd August 2016) - Song, Ju-Xian; Sun, Yue-Ru; Peluso, Ivana; Zeng, Yu; Yu, Xing; Lu, Jia-Hong; Xu, Zheng; Wang, Ming-Zhong; Liu, Liang-Feng; Huang, Ying-Yu; Chen, Lei-Lei; Durairajan, Siva Sundara Kumar; et al.
ABSTRACT: Autophagy dysfunction is a common feature in neurodegenerative disorders characterized by accumulation of toxic protein aggregates. Increasing evidence has demonstrated that activation of TFEB (transcription factor EB), a master regulator of autophagy and lysosomal biogenesis, can ameliorate neurotoxicity and rescue neurodegeneration in animal models. Currently known TFEB activators are mainly inhibitors of MTOR (mechanistic target of rapamycin [serine/threonine kinase]), which, as a master regulator of cell growth and metabolism, is involved in a wide range of biological functions. Thus, the identification of TFEB modulators acting without inhibiting the MTOR pathway would be preferred and probably less deleterious to cells. In this study, a synthesized curcumin derivative termed C1 is identified as a novel MTOR-independent activator of TFEB. Compound C1 specifically binds to TFEB at the N terminus and promotes TFEB nuclear translocation without inhibiting MTOR activity. By activating TFEB, C1 enhances autophagy and lysosome biogenesis in vitro and in vivo. Collectively, compound C1 is an orally effective activator of TFEB and is a potential therapeutic agent for the treatment of neurodegenerative diseases.